Sulforaphane has an additive anticancer effect to FOLFOX in highly metastatic human colon carcinoma cells - Čižauskaitė, Agnė; Šimčikas, Dainius; Schultze, Daniel; Kallifatidis, Georgios; Bruns, Helge; Čekauskas, Albertas; Herr, Ingrid; Baušys, Augustinas; Strupas, Kęstutis; Schemmer, Peter (Oncology reports, 2022)
Colorectal cancer (CRC) is one of the most common malignancies worldwide. Patients with CRC may need chemotherapy (CTx) in a neoadjuvant, adjuvant or palliative setting through the course of the disease. Unfortunately, its effect is limited by chemoresistance and chemotoxicity. Novel more effective and non‑toxic CTx regimens are needed to further improve CRC treatment outcomes. Thus, the present study was designed to test the hypothesis that non‑toxic sulforaphane (SF) is effective against CRC and has additive effects in combination with conventional 5‑fluorouracil, oxaliplatin and folinic acid (FOLFOX) CTx in vitro. Highly metastatic human colon cancer cells, CX‑1, and fibroblasts were treated with FOLFOX ± SF. Cell viability was assessed using an MTT assay. The level of apoptosis and the expression of apoptotic proteins were measured by TUNEL assay and quantitative PCR analysis. Aldehyde dehydrogenase isoform 1 (ALDH1) and multidrug resistance protein 2 (MRP2) levels were evaluated. The ability of cells to form spheroids was measured in three‑dimensional cell culture. SF alone and in combination with FOLFOX effectively decreased the viability of the CX‑1 cells, promoted apoptosis within the CX‑1 cells, prevented cellular spheroid formation and decreased ALDH1 activity. However, SF promoted MRP2 expression and protein levels. In conclusion, SF together with conventional FOLFOX has additive anticancer effects against highly metastatic human CRC in vitro.